Immunocytochemical characterization of primary cell culture in canine transmissible venereal tumor - Flórez, Luis M.M. [UNESP]; Ballestero, Haline F. [UNESP]; Duzanski, Anderson P. [UNESP]; Bersano, Paulo R.O. [UNESP]; Lima, João F. [UNESP]; Cruz, Fernanda L. [UNESP]; Mota, Ligia S.; Rocha, Noeme S. [UNESP] (FapUNIFESP (SciELO), 2016)
with anti-vimentin, anti-lysozyme, anti-alpha 1 antitrypsin, anti-CD3 and anti-CD79α antibodies has been used for characterization of primary cell culture in the transmissible venereal tumor (TVT). Samples for primary cell culture and immunohistochemistry assays were taken from eight dogs with cytological and clinical diagnosis of TVT. To validate the immunochemical results in the primary cell culture of TVT, a chromosome count was performed. For the statistical analysis, the Mann-Whitney test with p<0.05 was used. TVT tissues and culture cells showed intense anti-vimentin immunoreactivity, lightly to moderate immunoreactivity for anti-lysozyme, and mild for anti-alpha-antitrypsin. No marking was achieved for CD3 and CD79α. All culture cells showed chromosomes variable number of 56 to 68. This is the first report on the use of immunocytochemical characterization in cell culture of TVT. Significant statistic difference between immunochemistry in tissue and culture cell was not established, what suggests that the use of this technique may provide greater certainty for the confirmation of tumors in the primary culture. This fact is particularly important because in vitro culture of tumor tissues has been increasingly used to provide quick access to drug efficacy and presents relevant information to identify potential response to anticancer medicine; so it is possible to understand the behavior of the tumor.
Keywords: Alpha 1 antitrypsin; Canine transmissible venereal tumor; Cytogenetic; Lysozyme; Vimentin